The Competitiveness of SMK and Diploma 3 Graduates of Hospitality at the Entry Level and Employability Skills in Developing Career Pathways - Dalimunthe, Femmy Indriany; Sutadji, Eddy; Setianingsih, Rita Margaretha (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2016)
Along with the development of the ASEAN Economic Community in 2015, Indonesia is required to generate professional human resources in order to compete with other countries, particularly subject to competition in the services sector. Hotel is a product in the hospitality industry that have an important role in the tourism business.Intense competition in the hospitality industry demand the hotels to provide the best service to the customers. Vocational education has a function to prepare a professional and competitive workforce in the industry. The hospitality graduates will be able to fill the existing organizational structure in accordance with the educational background. The Presidential Decree No.8, 2012, Article 5 states that equalizing learning outcomes generated through education with the level of qualification at KKNI. KKNI is intended as a description of outcomes that must be mastered by graduates of vocational education, higher education, vocational training institutions as well as independent study. Graduates of Vocational and D3 of hospitality beganÂ their career in the hospitality industry by filling the positions in the organizational structure. In a few of star hotels in Medan, North Sumatra, hospitality graduates of vocational and D3 have competitive power in a very thin difference. Their entry level almost similar to the same position as well as employability skills and technical competence are almost equal that will provide a gap between the educational background of the career pathways that exist in the world of hospitality. It is very wise if there will be collaboration between the hotel industry, the educators, community leaders, and high-level policy makers in generating strategies to enhance the competitiveness of human resources professionals in the hospitality and placed in accordance with the level of education based KKNI.